Assessing Shock Volatility using Long Straddle Option Strategy: Evidence at IDX Composite - Riko Hendrawan (University of Merdeka Malang, 2018)
This study was to identify the probability of occurrence of shock volatility and was impact on return of an investment. Using IDX Composite data from 1998 to 2016 and long straddle option strategy at IDX composite consisting of two phases: high volatility daily return was 7 years with a total of 3432 observations, using 1716 call option simulation contracts, and 1716 put option simulation contracts and low volatility daily return were 12 years with a total of 5528 observations, using 2908 call option simulation contract and 2908 put option simulation contracts. The result showed that the shocking volatility occurs greater when the volatility below the average year of observation. Shock volatility during the year low volatility of 44.25% and period of year high volatility of 34.49%. But if calculated in total, based on 8960 observation from 1998-2016, where 4480 was call option and 4480 transactions were put transaction there were 1815 incident shock volatility or equal to 40.51. So the potential for profit (call and put option holders) or potential loss (call and put option seller) per day due to the occurrence of shock volatility of 40.51%.JEL Classification: G13, G17DOI: https://doi.org/10.26905/jkdp.v22i1.1707